Public Event: Brown Bag Lecture Series: This is not McLuhan’s Global Village - Ackerley, Christine Rose (Stream: Interdisciplinary Journal of Communication, 2016)
The School of Communication’s Brown Bag Lecture Series continues this month. Chaired by Yuezhi Zhao, "This is not McLuhan’s Global Village," will take place 12pm-1pm in the Mallinson Conference Room (K8652) on Wednesday, January 13th. Please see the full text for details.